Microsurgical reconstruction of complex maxillofacial gunshot wounds: Outcomes analysis and algorithm. Issue 5 (24th January 2019) - Gurunluoglu, Raffi; Gatherwright, James
Abstract : Background: Satisfaction with appearance, functional outcomes (speech, swallowing), work status after microsurgical reconstruction for maxillofacial gunshot wounds (GSW) remain largely unknown. The purpose of this study is to report these parameters. By investigating these outcomes, we also aimed to provide microsurgical algorithms for complex maxillofacial GSW. Methods: Forty‐two consecutive maxillofacial GSW patients between 2006 and 2014 were analyzed for outcomes. Mean age was 41.3 years ranging 14 to 77 years. There were 33 males and 9 females. Results: Twenty‐four patients received 36 free flaps for early reconstruction in 1 to 2 weeks, two patients in a delayed manner. Fifteen fibula flaps for mandible reconstruction, five fibula, there radial forearm (RF), and two scapular osteocutaneous (OC) flaps for maxilla reconstruction, two RF flaps for palate reconstruction, one RF for cheek reconstruction were used. Four patients underwent innervated gracilis flap for total lower lip and one for cheek reconstruction. Rectus abdominis myocutaneous flap was used for mid‐face defects in two patients. One anterolateral thigh flap was used for lower lip/chin reconstruction. Nine free flaps were performed to treat a complication and/or to improve function. All flaps survived except for three partial skin paddle loss to fibula flaps. Mean follow‐up was 17.2 months. Return to work/school was 70%. Surveys noted 58% "satisfied". All patients but two achieved perceptible speech, the majority had no difficulty with swallowing, all patients had oral competence. Conclusions: Favorable outcomes were obtained in most maxillofacial GSW. After investigating these outcomes, microsurgical algorithms were developed for clinical practice for reconstruction of composite mandible and total‐lower lip defects, and maxilla/mid‐face defects.